Explore BrainMass

Explore BrainMass

    Proving the Mod

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Prove that:
    if bd= bc (mod p) where p is a prime (and p does not divide b) , then d= c (mod p).

    © BrainMass Inc. brainmass.com December 24, 2021, 5:12 pm ad1c9bdddf

    Solution Preview

    Sol: bd = bc (mod p) implies that bc = bd + pk, where k is any integer.
    Dividing throughout by b, c = d + ...

    Solution Summary

    The solution assists with proving the mod.